Decentralisation of Financing of Self-Government Units in the Republic of Croatia - Emina Jerković (European Scientific Journal, ESJ, 2018)
Since its independence the Republic of Croatia has commenced a thorough reconstruction of its taxation system according to the market economy taxation policy. Essential taxation reforms have brought the system closer to EU systems i.e. it has been being harmonized with taxation systems of developed European countries. The Republic of Croatia has adopted solutions that are used by the majority of European countries. Current tax system of the Republic of Croatia can be viewed through three fiscal levels, but this paper deals with decentralization and revenue, especially tax revenue of local and regional self-government units. The paper will present importance and a way of collecting revenue, especially tax revenue and satisfying public needs in terms of counties, cities and municipalities. The local and central characteristics of the certain types of taxes and the specialities thereof, as well as the applied functional differences are also scrutinized, and a widely accepted opinion of the taxpayers is explained. Taking these into account, the scientific contribution of this paper is that it provides a basis for further research on tax system development.